Structural and optical properties of epitaxially laterally overgrown a-plane GaN epilayer on SiO2 stripe patterned r-plane sapphire - Lee, Yong Seok; Kim, Hun; Seo, Tae Hoon; Park, Ah Hyun; Lee, Seul Be; Chung, Sang Jo; Choi, Chel-Jong; Suh, Eun-Kyung (Electronic materials letters, 2013)
We have studied the structural anisotropic characteristics of epitaxially laterally overgrown (ELOG) a -plane GaN epilayer on r -plane sapphire substrate with two different SiO 2 -stripe orientations using metal organic chemical vapor deposition. The SiO 2 stipe patterns were made along [0001] and crystographilic orientations of GaN which correspond to and directions of r -plane sapphire, respectively. The ELOG a -plane GaN on [0001]-stripe orientation reveals symmetric morphology in the extent of lateral overgrowth compared to that grown on -oriented stripe. Threading dislocation and basal stacking fault densities in wing region were ∼8 × 10 7 cm −2 and ∼5.2 × 10 4 cm −1 , respectively. Raman measurement of the fully coalesced a-plane GaN indicated a compressive strain of about 0.39 Gpa in the window region.